2020
DOI: 10.3389/fonc.2020.00146
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Clinical Biochemistry-Based Indexes in Nasopharyngeal Carcinoma

Abstract: Inflammation and nutritional status have significant effects on the prognosis of cancer patients. This study investigated the predictive value of clinical biochemistry-based indexes in nasopharyngeal carcinoma (NPC). This retrospective study included 559 NPC patients and 500 patients with chronic rhinitis. Continuous variables were measured by t-test. The area under curves (AUC) was used to determine the diagnostic and prognostic value for NPC. Kaplan-Meier methods and the log-rank test were used to analyze ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…In the last few years, PNI has been extensively investigated as predictor of poor outcome in several types of cancer [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], including HNC [ 31 , 32 , 33 , 34 ]. Although a number of studies have evaluated PNI in relation to treatment toxicity [ 35 , 36 , 37 , 38 ], only few ones focused on HNC [ 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, PNI has been extensively investigated as predictor of poor outcome in several types of cancer [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], including HNC [ 31 , 32 , 33 , 34 ]. Although a number of studies have evaluated PNI in relation to treatment toxicity [ 35 , 36 , 37 , 38 ], only few ones focused on HNC [ 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, results from these emerging findings are inconsistent. For instance, some of them evinced that elevated AAPR was associated with poor survival outcomes [ 9 , 10 , 12 21 , 23 26 ], but others evinced that elevated AAPR was not correlated with survival outcomes [ 11 , 22 ]. Additionally, qualities of the above mentioned studies are variable, especially in terms of cancer types and methodology.…”
Section: Introductionmentioning
confidence: 99%
“…PNI is a biomarker based on serum albumin level and total lymphocyte count. Several evidences reported that PNI reflected the systemic immunonutritional status and was a prognostic indicator in various cancers, including gastric cancer [ 13 , 18 ], nasopharyngeal carcinoma [ 19 ], and lung cancer [ 20 , 21 ]. It was easily calculated in daily routine.…”
Section: Discussionmentioning
confidence: 99%